Effect of exogenous antibiotics on soil microbial community structure in tea garden - Xu Chenguang; Zhang Qichun; Hou Changping (浙江大学学报. 农业与生命科学版)
Antibiotics are medical drugs used to kill bacteria and treat infections. But in recent years, more and more antibiotics have been used in animal feed as growth promoters. Manure is used worldwide in agricultural practice as a fertilizer to enhance plant yields. Several studies revealed that manure also had a stimulating effect on the soil microbial biomass and community structure. However, in modern agriculture, the application of manure to field is very often combined with the spread of veterinary antibiotics. Tetracycline and penicillin are possible soil contaminants, since they are able to reach agricultural soils with manure of treated farm animals.Zhejiang Province is a major tea producing region in China, whose tea exports amount to 100 000 tons and production value accounts for one-third of the country. Every year a large number of organic fertilizers are put into the tea garden and the spread of veterinary antibiotics increases with applying organic fertilizer. The organic fertilizer can increase the yield of tea tree, but the harm to soils caused by antibiotics can not be avoided in the process of using organic fertilizer. Microorganism is a promoter of soil nutrient transformation, which plays an important role in maintaining balance, health and high quality of soil ecosystem. Although it has been confirmed that organic fertilizer (especially manure) application could promote the growth of crops, the impact of antibiotics by applying organic fertilizer on soil microbial community is still unknown. Thus, the aim of this research is to investigate possible toxic effects of antibiotic exposure on the indigenous bacterial community of tea garden.Topsoils (0-20 cm) were collected from Meijiawu Tea Village, Hangzhou, Zhejiang Province. Soils were spiked with a range of tetracycline or penicillin concentrations. The basic physicochemical properties of the tested soil were measured by routine analysis methods. The amounts of bacteria, fungi and actinomycetes of different treatments were calculated by plate count method. As we know, only 0.1%-10% microbes can be cultivated by this method, therefore we also used the method of phospholipid fatty acid (PLFA) to analyze the PLFAs contents to make a quantitative description of microbial community. After cultivation for three weeks, compared with the control treatment (CK), the amounts of bacteria, fungi and actinomycetes in P5 treatment (100 mg/kg) decreased by 80%, 50% and 50%, respectively. Soil microorganisms showed resistance to antibiotics after incubation for four weeks. The results of phospholipid fatty acid method showed that soil microbial community structure changed obviously under different contents of antibiotics treatments. The ratio of G-/G+ increased after antibiotic treatments. Principal component analysis showed different treatments located in four different quadrants. The content of PLFA 20:0 was rich in T3, T4 and T5 treatments.It is concluded that exogenous penicillin has certain inhibitory effect to bacteria, fungi and actinomycetes, and the inhibition increases with penicillin concentration. Tetracycline inhibits the growth of bacteria and actinomycetes in tea garden soil, but shows no obvious inhibitory effect against fungi. Inhibition of Gram-negative bacteria for both penicillin and tetracycline are stronger than Gram-positive bacteria. There is great difference in soil microbial community structure among different treatments. Microbes characterized by PLFA 20:0 may be the main groups of ant-i tetracycline microbes.